Effect of Traditional Chinese Medicine on Fish Growth: A Meta-Analysis Study - Salsabila, Salsabila; Muhammad, Almer Lutfi; Bayram, Muhammet; Suciyono, Suciyono (Universitas Airlangga, 2024)
Fish productivity has long been the subject of studies using traditional Chinese medicine (TCM). To validate TCM's effectiveness on weight gain rate (WGR) and specific growth rate (SGR), a meta-analysis study was conducted. Of the 58 studies collected from PubMed, Scopus, and Cochrane Library, 4 eligible studies were analyzed quantitatively. The extracted data were then analyzed using Review Manager (RevMan) online to determine the standard mean difference (SMD), random effect, heterogeneity, and 95% confidence intervals (95% CI). As a result, TCM administration had a favorable effect on WGR (SMD = 8.33; p = 0.0001) and SGR (SMD = 8.12; p = 0.0004). In conclusion, this meta-analysis study emphasized the efficacy of TCM to improve fish production performance.